Religiousness As A Shield In Corporate Tax Avoidance - Leon, Hengky; Apriyanto, Vito (JAS (Jurnal Akuntansi Syariah), 2024)
This study analyses the effect of asset structure, leverage, profitability, and sales growth on tax avoidance and uses religiosity as a moderating variable. The associative research focuses on 96 non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, with 34 companies selected using purposive sampling, resulting in 170 observations. The data comprises secondary data, including financial reports and Sharia stock list information. Data analysis using multiple linear regression and moderated regression analysis (MRA). The testing stages start from descriptive statistics, classical assumption testing, and hypothesis testing to evaluate the relationship between variables and the moderating role of religiosity in tax avoidance. The results reveal that asset structure, leverage, and profitability do not affect tax avoidance, while sales growth has a negative effect. Religiosity also demonstrates a positive effect on tax avoidance. The moderation results show that religiosity weakens the effect of asset structure and profitability on tax avoidance but does not moderate the influence of leverage. Conversely, religiosity strengthens the effect of sales growth on tax avoidance. This study can complement existing theories, and religiosity can be a key factor for future research in generating various hypotheses. This research can also be a reference for companies and stakeholders when determining tax policies.